2008
DOI: 10.1080/00222930701850380
|View full text |Cite
|
Sign up to set email alerts
|

The joint Swire Institute of Marine Science, Hong Kong, and Natural History Museum, London, Hong Kong Submarine Caves Expedition, 2002: discussion, conclusions and recommendations for conservation

Abstract: Some two hundred taxa have been recorded from Hong Kong's submarine caves. Of these, at least eleven are new to science. The majority of species occurring on the walls and roofs in particular, however, are not cave endemics and have been recorded from other habitats in Hong Kong and elsewhere. Unlike the Tethyan karsted limestone caves of Japan and the Philippines in the Asian region, and elsewhere, Hong Kong's cave fauna is similar to other local sea bed habitats at similar depths, probably because of their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ahermatypic corals were collected from Conic Island and Steep Island caves (for a description of the caves see Morton et al 2008) by divers and identified, wherever possible, to species.…”
Section: Methodsmentioning
confidence: 99%
“…Ahermatypic corals were collected from Conic Island and Steep Island caves (for a description of the caves see Morton et al 2008) by divers and identified, wherever possible, to species.…”
Section: Methodsmentioning
confidence: 99%
“…These descriptions are followed by interpretations of the species found and, hence, the communities identified. The implications of the findings with respect to the marine management and conservation of the caves are brought together in the final paper of these proceedings (Morton and Bamber 2008).…”
Section: Faunal Identifications and Conclusionmentioning
confidence: 98%